Penerapan Nilai-Nilai Moderasi Beragama Pada Pembelajaran Anak Usia Dini Di Ra Al-Mukminin Sukowono Jember Tahun Pelajaran 2021/2022 - Fajar Abdillah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Abstract: The diversity of a nation certainly creates its own challenges, especially in building harmony. It is not an easy to unite differences, because differences often lead to division and conflict. moreover, there are transnational notions that easily looking like a taghut disbelieve this nation-state and intolerant literalists. With these understandings, the potential for disintegration and acts of violence and terror is wide open to occur in our beloved country, Indonesia. Therefore, the inculcation of religious moderation values ​​occupies a strategic position among intolerant understandings. The inculcation of the values ​​of religious moderation through education for early childhood is increasingly urgent to be implemented. RA Al-Mukminin Sukowono, turns out to realize the importance of instilling the value of religious moderation in their students. Among what was done by the teacher RA Al-Mukminin Sukowono was instilling the value of tolerance by inserting it into appropriate themes. On that basis, it is important to know more about the application of religious moderation values ​​in RA al-Mukminin. On that basis, it is important to know more about the application of religious moderation values ​​in RA al-Mukminin. From the background above, the focus of research in this research is how to plan, implement, and evaluate the values ​​of religious moderation in early childhood learning at RA Al-Mukminin Sukowono Jember Academic Year 2021/2022. The purpose of this research is to describe how to plan, implement and evaluate the values ​​of religious moderation in RA al-Mukminin. This research uses descriptive qualitative method. The informant determination technique in this study used purposive sampling. Data collection techniques using observation, interviews and documentation. Data analysis using Miles and Huberman. The results of this study indicate that the application of religious moderation values ​​is divided into 3 stages, namely the planning, implementation and evaluation stages. At the planning stage the teacher prepares a daily lesson planning plan / RPPH which contains themes and SOPs that can be inserted into the values ​​of religious moderation. At the implementation stage, moderation values ​​in the form of tolerance are inserted in the theme of my country and national values ​​are inserted in the standard operating procedure (SOP). At the evaluation stage, the teacher evaluates using the non-test method, while the evaluation instrument uses conversation and giving assignments.